Corn Hybrid Response to Water Management Practices on Claypan Soil - Kelly A. Nelson; Randall L. Smoot (International Journal of Agronomy)
A study evaluated corn (Zea mays L.) hybrids (Asgrow785, DKC61-73, DKC63-42, LG2642, and Kruger2114) and water management systems (nondrained, nonirrigated (NDNI); drained, nonirrigated (DNI) with subsurface drain tiles 6.1 and 12.2 m apart; drained plus subirrigated (DSI) with tiles 6.1 and 12.2 m apart; nondrained, overhead irrigated (NDOHI)) on yields, plant population, and grain quality from 2008 to 2010. Precipitation during this study was 36 to 283 mm above the past decade. Planting date was delayed 18 d in the nondrained control in 2009, and additional delayed planting controls were included this year. Grain yields were similar in the 6.1- and 12.2 m-spaced DNI and DSI systems in 2008 and 2010, but plant population increased 74% and yields were 3.1 Mg ha−1 greater with DSI at a 6.1 m spacing compared to 12.2 m in 2009. At a 6.1 m spacing, DNI or DSI increased yield 1.1 to 6.6 Mg ha−1 (10 to over 50%) compared to NDNI or NDOHI soil. High yielding hybrids achieved similar yields with DNI, while NDNI DKC63-42 had 1.2 Mg ha−1 greater yields compared to DKC61-73. A 6.1 m spacing for DNI claypan soils is recommended for high yielding corn production.